Re-visiting the External Debt-Economic Growth Question in Zimbabwe - Mazorodze, Brian Tavonga (Journal of Economics and Behavioral Studies, 2020)
This paper quantifies the threshold effect of external debt on economic growth in Zimbabwe between 1980 and 2016. Results from the Fully Modified Ordinary Least Squares (FMOLS) technique confirm that external debt (up to 57% of GDP) raises economic growth. Beyond the 57% of GDP threshold, external debt lowers growth. A separate analysis of variance shows that the mean GDP per capita is lower by 11% when external debt exceeds 57%. From the sample average, the 57% of GDP threshold suggests that debt stock above 4.7 billion USD can be detrimental to the country’s long-run growth prospects. Currently, Zimbabwe’s external debt is standing at over 11 billion USD which is way above the estimated threshold level. Therefore, the policy implication arising from this paper is that the country’s Finance Minister needs to pursue debt-reduction strategies given that the country’s stock of external debt is already sitting in the growth-reducing territory.